Quantitative comparison of dose–effect and time–course of fluticasone furoate and fluticasone propionate in adult and adolescent patients with persistent asthma: A systematic review and meta‐analysis - Zhong, Ying; Li, Lujin; Chen, Rui; Zheng, Qingshan (Respirology (Carlton, Vic.), 2022)
This study aimed to quantitatively compare the efficacy of fluticasone furoate (FF) and fluticasone propionate (FP) in adolescents and adults with asthma. We searched the PubMed and EMBASE databases for placebo‐controlled trials that met the inclusion criteria. Pharmacodynamic models were established to describe the time–course of the primary outcome (trough forced expiratory volume in the first second [FEV1]). Secondary outcomes (asthma symptoms, quality of life and exacerbations) were also compared via a meta‐analysis. A total of 14 articles were included in the analysis, involving 6640 subjects. The efficacy plateau of the two drugs could be reached in 2 weeks. The changes from the baseline in trough FEV1 (95% CI) at week 2 of FF at 200 and 100 μg/day were 0.168 L (0.064–0.199) and 0.127 L (0.048–0.163), respectively. The changes from the baseline in trough FEV1 (95% CI) at week 2 of FP at 1000, 500, 250 and 100 μg/day were 0.133 L (0.049–0.171), 0.127 L (0.043–0.163), 0.117 L (0.039–0.150) and 0.093 L (0.032–0.129), respectively. The efficacy of FP had reached a plateau at the maximum evaluated dose (1000 μg/day), while a plateau effect was not seen at the maximum evaluated dose of FF (200 μg/day). In terms of secondary outcomes, the relative effects of the two drugs relative to the placebo were similar and did not show obvious dose–effect relationships. In this study, the time–course and dose–effect characteristics of FP, FF and placebo were quantitatively evaluated, providing necessary quantitative information for asthma‐related guidelines. Quantitative comparison of dose‐effect and time‐course of fluticasone furoate and fluticasone propionate in adult and adolescent patients with persistent asthma. See related editorial